The Promise and Peril of Post-MFA Apparel Production - Lopez-Acevedo, Gladys; Robertson, Raymond (World Bank, Washington, DC, 2012)
For anyone concerned about the effects of globalization on poverty in developing countries, the apparel sector in general and the end of the Multi-Fibre Arrangement (MFA) and the Agreement on Textiles and Clothing (ATC) in particular are key areas of interest. As an important first step toward industrialization, the apparel sector continues to provide an alternative for workers in low-wage agriculture or service jobs (especially less-skilled workers and women), even after other manufacturing sectors are established. By providing formal labor experience, these jobs hold the promise of lifelong participation in the labor market, which in the long term can help workers move out of poverty. Therefore, understanding how employment, wage premiums, and the structure of the apparel industry have changed after the end of the MFA and ATC is important to appreciate the effects of this significant policy change on poverty.